2021
DOI: 10.1108/ijlss-11-2020-0208
|View full text |Cite
|
Sign up to set email alerts
|

Experience of lean application in higher education institutions

Abstract: Purpose Recently, there has been an increasing interest in the concept of Lean; however, the Lean concept in higher education institutions (HEIs) is still not very popular, and these institutions face challenges in implementing Lean activities. The purpose of this study is to identify worldwide experiences of Lean implementation in HEIs and to share best practices of Lean implementation. Design/methodology/approach The research was conducted by surveying 34 Lean practitioners from HEIs. Findings This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Other factors are also suggested involving the creation of public value (Angiola et al, 2018), leadership and organizational culture (Ibrahim et al, 2018) and intellectual capital variables (Cricelli et al, 2018). Thus, these works demonstrate that performance in HEI remains as a knowledge gap in the literature and still needs further studies, especially involving Lean experiences (Simonyte et al, 2022). The present work explores this knowledge gap and advances by analyzing how the HEI Lean practices applicable to the public context influence the organizational performance.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Other factors are also suggested involving the creation of public value (Angiola et al, 2018), leadership and organizational culture (Ibrahim et al, 2018) and intellectual capital variables (Cricelli et al, 2018). Thus, these works demonstrate that performance in HEI remains as a knowledge gap in the literature and still needs further studies, especially involving Lean experiences (Simonyte et al, 2022). The present work explores this knowledge gap and advances by analyzing how the HEI Lean practices applicable to the public context influence the organizational performance.…”
Section: Introductionmentioning
confidence: 83%
“…However, in other areas, it is also common to verify Lean management initiatives, for example, in construction (Li et al, 2020), the public sector (Rodgers et al, 2021), in education (Cudney et al, 2020) and Higher Education Institutions (HEIs) (Francis, 2014;Antony et al, 2018;G omez-Molina and Moyano-Fuentes, 2022). In the latter, the use and knowledge of Lean management practices and the Lean system as a whole are still not very popular, although there are many successful cases of Lean implementation as described by Simonyte et al (2022). Petrusch et al (2019) understand that the implementation of Lean management practices has been primarily focused on process improvements rather than organizational change based on this philosophy's values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a current student project required other tools and methods than those included in the course, then they were free to search and find them (with the help of fellow students and teachers). Simonyte et al (2022), who studied lean in higher education institutions, propose that practitioners implementing lean should identify barriers, plan their activities and consider success factors. Results of this study revealed that managers need to deal with the main barrierthe complexity of the community and its processes, and the tackling of such barriers is a similar experience for most organizations (Cudney et al, 2011).…”
Section: Pedagogical Approach To the Implementation Of The Coursementioning
confidence: 99%
“…In opposition, in active learning methods students assume an active role in their own learning, while mentors are responsible for guiding apprentices through the learning process (Ramires et al, 2016;G omez-Molina and Moyano-Fuentes, 2021). Surprisingly, few publications evaluate LM teaching methods in terms of soft and hard skills learning (Merwe, 2017;Simonyte et al, 2021), featuring a gap in both theory and practice. Based on these arguments, we raise the following research question: RQ.…”
Section: Introductionmentioning
confidence: 99%